The evaluation of an oral health education program for midwives in Australia. Issue 3 (June 2016) - George, Ajesh; Lang, Gillian; Johnson, Maree; Ridge, Allison; de Silva, Andrea M.; Ajwani, Shilpi; Bhole, Sameer; Blinkhorn, Anthony; Dahlen, Hannah G.; Ellis, Sharon; Yeo, Anthony; Langdon, Rachel; et al.
Abstract: Background: Antenatal care providers are now recommended to promote oral health during pregnancy and provide dental referrals. However, midwives in Australia are not trained to undertake this role. To address this shortcoming, an online evidence based midwifery initiated oral health (MIOH) education program was systematically developed as a professional development activity. Aim: This study aimed to evaluate the effectiveness of the program in improving the oral health knowledge of midwives and assess their confidence to promote maternal oral health post training. Methods: The program was evaluated using a pre–post test design involving 50 midwives purposively recruited from two states in Australia. The pre–post questionnaire contained 24 knowledge items previously pilot tested as well as items exploring confidence in promoting oral health and perceptions of the program. Findings: The results showed a significant improvement in the oral health knowledge (↑21.5%, p < 0.001) of midwives after completion of the program. The greatest improvement in knowledge occurred in key areas vital in promoting maternal oral health namely the high prevalence of dental problems and its impact on birth and infant outcomes. The majority also reported being confident in introducing oral health into antenatal care (82%) and referring women to dental services (77.6%) after undertaking the education program. Conclusion: The MIOH education program is a useful resource to equip midwives with the necessary knowledge and skills to promote oral health during pregnancy. The program is accessible and acceptable to midwives and can potentially be transferable to other antenatal care providers.